COVID-19 vaccine acceptance, hesitancy and refusal among Iraqi Kurdish population - Tahir, Arazoo Issa; Ramadhan, Dilkhosh Shamal; Piro, Safiya Sabri; Abdullah, Rebar Yahya; Taha, Ari Ahmed; Radha, Runak Hamagharib (International Journal of Health Sciences, 2021)
Objectives: Vaccination is one of the most significant public health achievements of humanity. However, a significant portion of the population remains hesitant about vaccine safety, efficacy, and necessity. This study aimed to determine COVID-19 vaccination intention and factors affecting their decision among the general population in the Kurdistan region, Iraq. Methods: A cross-sectional survey was conducted online during (April-May 2021), and a total of 1171 participants provided complete and valid answers were enrolled. Data collection was done through online questionnaire through Google Forms. We used binary regression analysis to identify factors associated with COVID-19 vaccination intention. Results: The majority (53.6%) of the participants were female. Willingness to accept COVID-19 vaccine was low (33 %) of the participants. We found that vaccine hesitancy/resistance was high which was evident for (32%) and (34.9%) of surveyed populations, respectively. Vaccination intention may associate with age, education, and occupation. Furthermore, several factors were associated with hesitancy/resistance: Adverse effects of the vaccine and loss of family members during the pandemic. Conclusions: More than half of the study participants refused or were hesitant to have the COVID-19 vaccine, so that Governments and health authorities should improve communication and increase trust.